Perspektif Hukum Islam terhadap Biaya Administrasi Transfer Dana melalui BSI Mobile - Wahyuda, Agung Taufik; Batubara, Enika; Dhar, Ali Ad; Rodiah, Rindur; Chasnun, Faiz Nayla (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The presence of Islamic banks in Indonesia since the late 19th century and their development to the present day has helped us understand the importance of Islamic economics in Indonesia. This research uses library research methods, collecting data or scholarly writings as the research object, gathering library data, or studies conducted to solve a problem. The Fiqh Muamalah analysis shows that fund transfer transactions between banks through the BSI Mobile application are allowed because they avoid riba, maisir, gharar, tadlis, and facilitate fund transfer transactions between different banks. In addition, the contracts used are also in accordance with the Fatwa DSN MUI No. 10/DSN-MUI/IV/2000 on Wakalah and Fatwa DSN MUI No. 113/DSN-MUI/IX/2017 on Wakalah bi al-Ujrah.